2020
DOI: 10.3390/rs12060909
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Automatic Methodology for Fire Break Maintenance Operations Detection with Sentinel-2 Imagery and Artificial Neural Network

Abstract: The difficult job of fighting fires and the nearly impossible task to stop a wildfire without great casualties requires an imperative implementation of proactive strategies. These strategies must decrease the number of fires, the burnt area and create better conditions for the firefighting. In this line of action, the Portuguese Institute of Nature and Forest Conservation defined a fire break network (FBN), which helps controlling wildfires. However, these fire breaks are efficient only if they are correctly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…In a recent study, an object-based approach for FB fuel treatment detection suggested that most discriminant vegetation indices for classification were based on visible bands, using B05, the excess of green and excess of red indices [19]. Our comparison between NDVI and MExG results did not confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In a recent study, an object-based approach for FB fuel treatment detection suggested that most discriminant vegetation indices for classification were based on visible bands, using B05, the excess of green and excess of red indices [19]. Our comparison between NDVI and MExG results did not confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 80%
“…However, this requires a good empirical knowledge of the change signal and duration, which is not feasible in this study due to the diversity of climate, soil, species and vegetation phenology responses and land use types present in FB [18]. Object-based detections have the advantage to use spatial information but require a reliable segmentation, which limits their utility in the case of FB, where fuel treatments may have variable geometries over the years [19]. The Copernicus Sentinel-2 multispectral instrument (S2) from the European Space Agency (ESA) [20] has its first four bands at 10 m resolution and, since the launch of a second satellite in 2017, a 5 day revisit period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as it can be observed in Figure 7, errors are introduced in the final change detection product due to the misregistration of Sentinel-2 images (middle row). Several studies have also identified that Sentinel-2 orthoimages may have geolocation offset errors, especially at higher spatial scale (10m bands) (Kukawska et al, 2017;Pereira-Pires et al, 2020;Yan et al, 2018). The effect of the misregistration might be important when employing multi-temporal Sentinel-2A data for applications that require precise sub-pixel registration suggesting the use of additional pre-processing steps (Pereira-Pires et al, 2020;Yan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also identified that Sentinel-2 orthoimages may have geolocation offset errors, especially at higher spatial scale (10m bands) (Kukawska et al, 2017;Pereira-Pires et al, 2020;Yan et al, 2018). The effect of the misregistration might be important when employing multi-temporal Sentinel-2A data for applications that require precise sub-pixel registration suggesting the use of additional pre-processing steps (Pereira-Pires et al, 2020;Yan et al, 2018). Finally, the Sen2Cor processor, as indicated in previous studies, presents moderate accuracy in cloud/shadow removal, including over-detection of clouds over bright targets and degraded performance for scenes with low clouds (Baetens et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation